MV Wakashio grounding incident in Mauritius 2020: The world's first major spillage of Very Low Sulfur Fuel Oil - Scarlett, Alan; Nelson, R.K.; Gagnon, Monique; Holman, Alex; Reddy, C.M.; Sutton, P.A.; Grice, Kliti (2021)
Very Low Sulfur Fuel Oils (VSLFO, <0.5% S) are a new class of marine fuel oils, introduced to meet recent International Maritime Organization regulations. The MV Wakashio was reported to have released 1000 t of VLSFO when it grounded on a reef in Mauritius on 25th July 2020. A field sample of oily residue contaminating the Mauritian coast was collected on 16th August 2020 and compared with the Wakashio fuel oil. Both oils were analyzed for organic and elemental content, and stable isotope ratios δ13C and δ2H measured. Comprehensive two-dimensional gas chromatography with high-resolution mass spectrometry was used to identify and compare biomarkers resistant to weathering. The aromatic content in the VLSFO was relatively low suggesting that the potential for ecosystem harm arising from exposure to toxic components may be less than with traditional fuel oil spills. The Wakashio oil spill is, to our knowledge, the first documented spill involving VLSFO.